Mesoarchean exhumation of the Akia terrane and a common Neoarchean tectonothermal history for West Greenland - Kirkland, Chris; Yakymchuk, C.; Hollis, Julie; Heide-Jørgensen, H.; Danišík, M. (Elsevier BV, 2018)
© 2018 The Authors Recent geochronological and petrographic studies in the Nuuk region, West Greenland, have established that modern-style tectonic processes were active in the Neoarchean. However, more limited work has addressed Neoarchean processes elsewhere in West Greenland. In particular, conflicting models have been proposed for the tectonothermal history of the Akia terrane, to the north of the Nuuk region. In this study, the depositional and metamorphic history of supracrustal rocks in the Akia terrane have been investigated using field relationships, petrography, phase equilibria modelling, and zircon and apatite U-Pb geochronology. The Akia terrane is a Palaeo- to Mesoarchean tonalite-trondhjemite-granodiorite (TTG) gneiss terrane with subordinate supracrustal rocks, mafic to ultramafic intrusions – all metamorphosed at amphibolite to granulite facies – Proterozoic mafic dyke suites, Neoproterozoic and Jurassic kimberlitic rocks, and a Mesoarchean and a Jurassic carbonatite. Some of the supracrustal rocks are known to be Mesoarchean, whilst others lack age constraint. New detrital and metamorphic zircon ages show that the metasedimentary rocks studied – the Kangerluarsuk Supracrustal Belt – were sourced from TTG gneisses within the host Akia terrane and deposited in the period =2877 Ma to =2857 Ma; this requires exhumation of the Akia terrane after c. 3010–2970 Ma magmatism and low-pressure granulite facies metamorphism. After exhumation, the Kangerluarsuk Supracrustal Belt was buried and underwent prolonged high-temperature metamorphism, reaching ~820–850 °C and 8–10 kbar during regional ductile deformation in the period 2857–2700 Ma. The same rocks grew metamorphic zircon and neoblastic apatite at c. 2630 Ma and >450 to <850 °C, based on U-Pb geochronology and Pb diffusion modelling respectively. This evidence of Neoarchean metamorphism of the Akia terrane shows that a large part of West Greenland was in tectonic communication and experienced common high temperature conditions in the latest Mesoarchean to early Neoarchean and by c. 2700 Ma. The recognition of prolonged Neoarchean high-temperature metamorphism and partial melting during regional ductile deformation raises questions about the veracity of textural evidence for a giant bolide impact at =3000 Ma in the same region as such evidence would likely have been obliterated through such pervasive metamorphic and tectonic reworking.